The Influence of Celebrity Endorsements and Social Media Marketing on Purchase Intention Through Brand Image (Study on Yotta Beverage Consumers in Makassar City) - Zanna Arsyad, Miftahul; Sudarmiatin Sudarmiatin; Sopiah Sopiah (Pusat Riset dan Inovasi Nasional, 2023)
As business competition is getting tougher, endorsement programs and social media marketing are marketing strategies that are quite effective for providing promotions while reminding more consumers to relate to brands and encouraging consumer purchase intentions. This study aims to determine the effect of celebrity endorsements and social media marketing on purchase intention through brand image. The population in this study is prospective consumers who know Yotta products. While the sample in this study was 224 respondents. This type of research is descriptive and non-probability, using the Smart PLS program. The results are (1) program endorsement has a positive and significant effect on the brand image (2) social media marketing has a positive and significant effect on brand image and purchase intention (3) has no positive and significant effect on program endorsement on purchase intention (4) has a positive and significant effect brand image on purchase intention. Based on the results of the study, similar business actors suggest that companies be more selective in using celebrity programs to promote their products